1987
DOI: 10.1002/jcp.1041330222
|View full text |Cite
|
Sign up to set email alerts
|

Heparin potentiates the action of plasma membrane‐associated growth stimulatory activity

Abstract: Plasma membranes prepared from mouse liver have been previously shown to contain growth stimulatory activity as determined with cultured mouse fibroblasts. This growth stimulatory activity, termed plasma membrane-associated growth stimulatory activity (PMGA), is highly mitogenic in the presence of platelet-poor plasma. We now demonstrate that the growth stimulatory action of PMGA is dramatically enhanced by the addition of heparin. The half-maximal effect of heparin was observed at 1-3 micrograms/ml. The syner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1988
1988
1992
1992

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…Gel-purified mitogen, which is highly mitogenic for Schwann cells and oligodendrocytes, had no effect on the proliferation of NR6-3T3 fibroblasts, GFAPt astrocytes, or OX42+ microglia. The inability of the mitogen to stimulate NR6-3T3 cells, which proliferate vigorously in response to acidic and basic FGF (Nagasaki and Lieberman, 1987), clearly distinguishes the mitogen from previously described FGFs. This result corroborates our previous data showing that antibodies that recognize and immunoprecipitate bFGF are unable to deplete activity from mitogenic extracts (Ratner et al, 1988).…”
Section: Gel-purified Mitogen Stimulates the Proliferation Of Cells Omentioning
confidence: 90%
“…Gel-purified mitogen, which is highly mitogenic for Schwann cells and oligodendrocytes, had no effect on the proliferation of NR6-3T3 fibroblasts, GFAPt astrocytes, or OX42+ microglia. The inability of the mitogen to stimulate NR6-3T3 cells, which proliferate vigorously in response to acidic and basic FGF (Nagasaki and Lieberman, 1987), clearly distinguishes the mitogen from previously described FGFs. This result corroborates our previous data showing that antibodies that recognize and immunoprecipitate bFGF are unable to deplete activity from mitogenic extracts (Ratner et al, 1988).…”
Section: Gel-purified Mitogen Stimulates the Proliferation Of Cells Omentioning
confidence: 90%
“…On the one hand, heparin has been shown to restore the biological activity of old preparations of aFGF and bFGF [14], to protect aFGFs from proteolysis [23,29] and heat inactivation [14] and to prolong its biological half-life [3]. On the other hand, it has been shown that heparin potentiates the action of plasma membrane-associated growth stimulatory activity [24] and modulates the binding of bFGF to bovine brain membranes since this binding is reduced by 75°70 after heparinase treatment [4]. In our experiments, aFGF alone stimulated the proliferation of sparsely seeded EC and retained the same activity throughout the lesion repair experiments (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…NR6 cells, an epidermal growth factor receptor-negative variant of Swiss 3T3 cells (14), were used to assay mitogenicity of FGF as described (15).…”
mentioning
confidence: 99%